Synthesis of Galactosyl Mannitol Derivative Using β-Galactosidase from Kluyveromyces lactis - Klewicki Robert; Belina Iwona; Wojciechowska Aleksandra; Klewicka Elżbieta; Sójka Michał (Polish Journal of Food and Nutrition Sciences)
The purpose of the study was to identify the influence of reactive mixture concentration (23–48 g/100 mL), pH (6.5–9.0), presence of NaCl (0.05–0.25 mol/L) and enzyme dose (2850–28,500 LAU/100 g of lactose) on the synthesis of galactosyl mannitol derivative using β-galactosidase from Kluyveromyces lactis. The use of the enzyme dose ranging from 2850 to 11,400 LAU/100 g lactose allowed obtaining gal-mannitol at the level of 21.8% total saccharides; higher doses intensified product decomposition. An increase in the concentration of the reactive mixture had a positive impact on the quantity of gal-mannitol obtained every single time, i.e. 4.39 g were obtained from 100 mL of a 23 g/100 mL solution and over 10 g were obtained from a 48 g/100 mL solution. A relatively low increase in product quantity (by ca. 5%) occurred after the pH was increased from 6.5 to 9.0. The use of NaCl rendered better results. An increase in the maximum content of gal-mannitol in the total sugar by 12.8% was observed at the concentration of 0.25 mol/L.